Exploring the Impact of ISO 9001, ISO 14001 and OHSAS 18001 Certification on Financial Performance: The Case of Companies listed on the Bucharest Stock Exchange - Mihaela Ionașcu; Ion Ionașcu; Marian Săcărin; Mihaela Minu (Amfiteatru Economic Journal, 2017)
The purpose of this paper is to investigate the impact of ISO 9001, ISO 14001 and OHSAS 18001 certification on the financial performance of Romanian companies listed on the Bucharest Stock Exchange (BSE). Based on audited financial statements of a population of 67 non-financial companies listed during 2013-2015 and using regression models, this paper shows, for the first time in Romania, that companies listed on BSE, implementing complex management systems (quality – environmental and/or occupational health and safety) perform better, and that their performance is directly linked to the complexity of the management systems implemented.
Keywords: D29; L25; M19; M41; 330; ISO 9001; ISO 14001; OHSAS 18001; quality management; environmental management; occupational health and safety management; financial performance